Pelatihan Preposisi Tempat Bahasa Inggris In, On, dan At Untuk Siswa Lembaga Pendidikan Pramugari Total Source Development Yogyakarta - Wijayanti, Anita; Jaya, I Made Laut Mertha; Pujianto, Defi (EBBANK, 2025)
Prepositions are a topic in English that is considered difficult to master. Linguistic differences between Indonesian and English are considered one of the reasons why Indonesian English speakers find it difficult to use the correct English prepositions. Confusions often arise when Indonesian learn the prepositions of place in, on, and at, because in Indonesian, all three are translated as the preposition "di." The author found that students at the Total Source Development Flight Attendant Training Institute in Yogyakarta had difficulty using the prepositions of place in, on, and at correctly. Therefore, the writer decided to start a community service at the institute to help the students master this topic. Due to the limited time for preparation and execution, the writer decided to use a lecture-based teaching method. To help students overcome the boredom commonly associated with this method, the writer also included a Microsoft PowerPoint presentation to make the class more engaging. Students were also given the opportunity to participate actively by asking and answering questions during the lesson. By the second day, students were found to be able to use the prepositions of place in, on, and at quite well in conversation.